Candidates' attractiveness in selection decisions: a laboratory experiment. Issue 4 (2nd October 2017) - Cristofaro, Matteo
Abstract : Purpose: Recruiters in today's organizations, through social networks, have the opportunity to see a candidate's overall figure, and from this, they gain a first impression of their personalities which in turn affects their decisions. The purpose of this paper is to investigate the biasing role of candidates' attractiveness – in facial and bodily terms – on perceived main personality features (i.e. core evaluations (CEs)) in selection decisions. Design/methodology/approach: An experimental study involving professional recruiters ( n =150) was conducted. Participants were asked to rate bodily attractiveness (using the objectification construct), CEs, facial attractiveness and hiring scores of six candidates for an administrative position; then, a moderated mediation model was tested. Findings: This study suggests that recruiters' perception of candidates' CEs mediates the relationship between objectification (i.e. body attractiveness) and the assigned hiring score, while facial attractiveness amplifies or reduces the effect of objectification on CEs. Originality/value: The value added of this contribution lies in studying the biasing mechanism of candidates' overall attractiveness (facial and bodily) and its effects on the perceived core personality features.